Experiences of breastfeeding peer counseling among women with low incomes in the US: a qualitative evaluation - Elizabeth C. Rhodes; Mahrukh Zahid; Nafeesa Abuwala; Grace Damio; Helen Wilde LaPlant; Carrianne Crummett; Rebecca Surprenant; Rafael Pérez-Escamilla (BMC, 2024)
Abstract Background Person-centered breastfeeding counseling is a key but often overlooked aspect of high-quality services. We explored women's experiences of the Breastfeeding Heritage and Pride™ program, an evidence-based breastfeeding peer counseling program serving women with low incomes in the United States. Methods This study was conducted through an equitable community-clinical-academic partnership and guided by the World Health Organization (WHO) quality of care framework for maternal and newborn health, which highlights three domains of positive experiences of care: effective communication; respect and dignity; and emotional support. In-depth interviews were conducted with a purposive sample of women participating in the Breastfeeding Heritage and Pride™ program. Women were asked to describe their experiences with the program including examples of when good quality counseling was or was not provided. Each interview was conducted in English or Spanish, audio-recorded, and transcribed verbatim. Data were analyzed using reflexive thematic analysis. Once themes were generated, they were organized according to the three care experience domains in the WHO quality of care framework. Results Twenty-eight in-depth interviews were conducted with a racially/ethnically and socio-economically diverse sample of women. Three themes described effective communication practices of peer counselors: tailoring communication to meet women's individual needs; offering comprehensive and honest information about infant feeding; and being timely, proactive, and responsive in all communications across the maternity care continuum. Two themes captured why women felt respected. First, peer counselors were respectful in their interactions with women; they were courteous, patient, and non-judgmental and respected women's infant feeding decisions. Second, peer counselors showed genuine interest in the well-being of women and their families, beyond breastfeeding. The key theme related to emotional support explored ways in which peer counselors offered encouragement to women, namely by affirming women's efforts to breastfeed and by providing reassurance that alleviated their worries about breastfeeding. These positive experiences of counseling were appreciated by women. Conclusions Women described having and valuing positive experiences in their interactions with peer counselors. Efforts to expand access to high-quality, person-centered breastfeeding counseling should, as part of quality assurance, include women's feedback on their experiences of these services.